Unity of Spirit : Studies on William Of Saint-Thierry in Honor of E. Rozanne Elder - Sergent, F. Tyler; Elder, E. Rozanne (Ellen Rozanne), 1940- (Book collections on Project MUSE., 2015)
William of Saint-Thierry (ca. 1080-148) became abbot of the Benedictine abbey of Saint-Thierry in about 1119, holding that office for about sixteen years and writing a large number of works, some for the guidance of the monks of his abbey and others as theological treatises. But during that same time, after meeting Bernard, abbot of the Cistercian abbey of Clairvaux, he longed to become a Cistercian. He finally satisfied that dream in 1135, when he became a monk at Signy. His final work was the first of the five books that constitute the Vita Prima Sancti Bernardi. The nine chapters in this book explore William's thought as represented in his twenty works, ranging from his earliest theological writing through his contribution to the Vita Prima Sancti Bernardi. The contributors to this volume have moved scholarship on William in new directions, ranging from a comparative analysis of Bernard's and William's thought through a study of William's Christology, an analysis of individual works, a new translation of one of William's little-known works, an examination of sixteenth-century images drawn from the Vita Prima, a study of William's rhetorical skills, and a recognition of William's new take on the phrase "unitas spiritus." Dr. E. Rozanne Elder's expertise as a scholar of the works of William of Saint-Thierry, combined with her decades of distinguished service as a professor of history, director of the Institute of Cistercian Studies and then of the Center for Cistercian and Monastic Studies, all at Western Michigan University, and as editorial director of Cistercian Publications for thirty-five years, has made her the best known of Cistercian scholars today. She is the one primarily responsible for moving Cistercian studies into the mainstream of medieval history and thought.